Autonomy and the limits of cognitive enhancement. (22nd July 2020) - Lewis, Jonathan
Abstract: In the debates regarding the ethics of human enhancement, proponents have found it difficult to refute the concern, voiced by certain bioconservatives, that cognitive enhancement violates the autonomy of the enhanced. However, G. Owen Schaefer, Guy Kahane and Julian Savulescu have attempted not only to avoid autonomy‐based bioconservative objections, but to argue that cognition‐enhancing biomedical interventions can actually enhance autonomy. In response, this paper has two aims: firstly, to explore the limits of their argument; secondly, and more importantly, to develop a more complete understanding of autonomy and its relation to cognitive enhancement. By drawing a distinction between the capacity for autonomy and the exercise and achievement of autonomy, and by exploring the possible effects of cognitive enhancement on both competence and authenticity conditions for autonomy, the paper identifies and explains which dimensions of autonomy can and cannot, in principle, be enhanced via direct cognitive interventions. This allows us to draw conclusions regarding the limits of cognitive enhancement as a means for enhancing autonomy.